Role of Social Factors in Promoting Premarital Sex in Central Division Kabale Municipality. - Nansubuga, Maryliz (Kabale University, 2024)
This study investigated the role of social factors in promoting premarital sex among children in Central Division, Kabale Municipality. Premarital sexual activities among young people have been a growing concern due to the associated negative social, health, and psychological impacts. The study sought to understand the underlying social factors contributing to this behavior, assess the impact on children, and propose possible solutions to address the root causes The objectives of the study were threefold: first, to identify the social factors that contribute to the prevalence of premarital sex among children in Kabale Municipality; second, to assess the impact of premarital sex on these children, including emotional, physical, and societal consequences; and third, to explore potential interventions or solutions to mitigate the influence of social factors that encourage this behavior. Findings from this research are expected to contribute to a better understanding and management of the issue, guiding policymakers, educators, and community leaders in implementing effective strategies to reduce premarital sexual activity among young people in Kabale Municipality.